Tamoxifen persistently disrupts the humoral adaptive immune response of gilthead seabream (Sparus aurata L.). Issue 2 (December 2015) - Rodenas, M.C.; Cabas, I.; Abellán, E.; Meseguer, J.; Mulero, V.; García-Ayala, A.
Abstract There is increasing concern about the possible effect of pharmaceutical compounds may have on the fish immune system. Bath exposition of 17α-ethynylestradiol (EE2), a synthetic estrogen used in oral contraceptives, altered the immune response of the gilthead seabream (Sparus aurata L.), a marine hermaphrodite teleost. Tamoxifen (Tmx) is a selective estrogen-receptor modulator used in hormone replacement therapy, the effects of which are unknown in fish immunity. This study aims to investigate the effects of dietary administration of EE2 (5 μg/g food) and Tmx (100 μg/g food) on the immune response of gilthead seabream, and the capacity of the immune system to recover its functionality after a recovery period. The results show for the first time the reversibility of the effect of EE2 and Tmx on the fish immune response. Tmx promoted a transient alteration in hepatic vitellogenin gene expression of a different magnitude to that produced by EE2. Both, EE2 and Tmx inhibited the induction of interleukin-1β gene expression while reversed the inhibition of ROI production in leukocytes following vaccination. However, none of these effects were observed after ceasing EE2 and Tmx exposure. EE2 and Tmx stimulated the antibody response of vaccinated fish although Tmx, but not EE2, altered the antibody response and modulated the percentage of IgM+ B lymphocytes of vaccinated fish during the recovery phase. Taken together, our results suggest that EE2 and Tmx might alter the capacity of fish to appropriately respond to infection and show that Tmx has a long-lasting effect on humoral adaptive immunity.